2020
DOI: 10.1371/journal.pone.0241468
|View full text |Cite
|
Sign up to set email alerts
|

Human mobility trends during the early stage of the COVID-19 pandemic in the United States

Abstract: In March of this year, COVID-19 was declared a pandemic, and it continues to threaten public health. This global health crisis imposes limitations on daily movements, which have deteriorated every sector in our society. Understanding public reactions to the virus and the non-pharmaceutical interventions should be of great help to fight COVID-19 in a strategic way. We aim to provide tangible evidence of the human mobility trends by comparing the day-by-day variations across the U.S. from January 2020 to early A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
127
3
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(141 citation statements)
references
References 33 publications
7
127
3
4
Order By: Relevance
“…In this study, we report and analyze various lockdown-induced changes in mobility in Germany during the initial phase of the COVID-19 pandemic. We found a considerable reduction of mobility during the pandemic, similar to what was previously reported for other countries that passed and implemented comparable policies ( 8 11 ). The reduction in mobility can be divided into a swift decrease, early in the lockdown phase, followed by a slow recovery.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this study, we report and analyze various lockdown-induced changes in mobility in Germany during the initial phase of the COVID-19 pandemic. We found a considerable reduction of mobility during the pandemic, similar to what was previously reported for other countries that passed and implemented comparable policies ( 8 11 ). The reduction in mobility can be divided into a swift decrease, early in the lockdown phase, followed by a slow recovery.…”
Section: Discussionsupporting
confidence: 89%
“…Based on various digital data sources such as mobile phone data or social media data, several studies show that mobility significantly changed during lockdowns ( 7 ). Most studies focused on general mobility trends and confirmed an overall reduction in mobility in various countries ( 8 – 12 ). Other research focused on the relation between mobility and disease transmission: For instance, it has been argued that mobility reduction is likely instrumental in reducing the effective reproduction number in many countries ( 13 17 ), in agreement with theoretical models and simulations, which have shown that containment can effectively slow down disease transmission ( 18 20 ).…”
mentioning
confidence: 99%
“…The third, the country of study and the references. Category Proxy data type Country and reference Adoption of NPI Mobile phones and/or vehicles through location intelligence and measurement platforms USA [367] , [368] , [369] , [370] , [371] , [372] Twitter Twitter population [373] , [374] Wikipedia and Reddit Canada, Italy, USA, UK [375] Google USA [376] ; 130 countries [377] TV USA [378] Mobility changes Mobile phones and/or vehicles through location intelligence and measurement platforms USA [37] , [38] , [379] , [380] Facebook Italy [39] Citymapper app 22 countries [381] …”
Section: Measuring Npis Via Proxy Datamentioning
confidence: 99%
“…The importance of socio-demographic and socio-economic characteristics in the adoption of NPIs has been also reported in other studies conducted by monitoring variations to aggregate mobility patterns before and during NPIs. Unanimously they indicate that disadvantaged groups, though less mobile before the pandemic, were not able to reduce their mobility (i.e., stay home) during the implementation of strict NPIs [30][31][32][33][34][35][36][37]. The literature aimed at estimating the epidemiological and societal impact of COVID-19 vaccines has been focused mainly on two very important points.…”
Section: Introductionmentioning
confidence: 99%